2015
DOI: 10.15376/biores.10.3.3922-3933
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Pretreatments of Switchgrass Leaf and Stem Fractions to Increase Methane Production

Abstract: The objective of this study was to determine the effectiveness of microwave pretreatments on methane production from two switchgrass tissues (leaf vs. stem). The methane production from the leaf fraction was significantly affected by the microwave final temperature, while production from the stem fraction was affected by the combination of the microwave final temperature and heating rate. Thus, the highest methane yield from the leaf (134.81 mL CH4/g of volatile solids (VS)) was obtained at 100 °C, while the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…According to information in Table 3, physical methods appear to be the fastest amongst the pretreatment methods. This is more so for microwave (MW) pretreatment (Wu et al, 2015;Kumar and Sharma, 2017). This is in agreement with Yuan et al…”
Section: Science Direct Ebscohost Pubmed Totalsupporting
confidence: 90%
See 1 more Smart Citation
“…According to information in Table 3, physical methods appear to be the fastest amongst the pretreatment methods. This is more so for microwave (MW) pretreatment (Wu et al, 2015;Kumar and Sharma, 2017). This is in agreement with Yuan et al…”
Section: Science Direct Ebscohost Pubmed Totalsupporting
confidence: 90%
“…Physical pretreatment appears to be generally effective as shown in Table 5. For example, hot water pretreatment increased methane yield from rice straw by 222% (Ge et al, 2016) and MW method increased methane yield by 28% (Wu et al, 2015). Baeta et al (2016) reported that autohydrolysis is a highly effective process.…”
Section: Effectivenessmentioning
confidence: 99%
“…However, the methane production of the above groups was higher than those of other results. For example, the reported methane production values of switchgrass leaves and stems were 134.81 and 99.35 mL/g VS, respectively, when they were fermented by municipal sludge at 37 °C for 60 days . Another study using a biogas slurry as the sole inoculum achieved methane production of 135.31 mL/g VS at 35 ± 1 °C after 44 days of fermentation from switchgrass …”
Section: Results and Discussionmentioning
confidence: 99%
“…At the initial stage of fermentation, gas production and composition were measured every other day as their changes were obvious. Gas production was monitored using the saturated brine displacement method . Liquid samples were collected every few days and were kept at −20 °C to test other indicators.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The microwave digestion vessel of CEM Corporation uses Teflon as lining, advanced composite materials as outside material which increases pressure resistance and can ensure high pressure and temperature required for pretreatment. The temperature and pressure in the vessel could be monitored with sensors (Fan et al, 2013;Hu and Wen, 2008;Jackowiak et al, 2011a;Jackowiak et al, 2011b;Li et al, 2014c;Wu et al, 2015). The digestion vessel of Milestone Co. uses tetrafluorometoxil (TFM) material, which is an analog of Teflon but with a better property in some ways (Chen et al, 2012a;Lu and Zhou, 2011).…”
Section: Microwave Penetration Vesselmentioning
confidence: 99%